PENGARUH KEPEMILIKAN INSTITUSIONAL, FREE CASH FLOW, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN UTANG PERUSAHAAN (Studi Empiris Perusahaan Yang Terdaftar Di BEI 2010-2018) - Robiansyah, Anton; Andre Suandi Simbolon; Steviani Batti (Distribusi - Journal of Management and Business, 2020)
This study aims to empirically examine the effect of institutional ownership structure, free cash flow, and company size on debt policy. Free Cash Flow is measured by FCF proxy, which is operating cash flow minus capital expenditure minus changes in working capital and then compared to total assets. The population used in this study are all companies listed on the Indonesia Stock Exchange (IDX) and limited to consumer goods companies as well as primary and chemical industries that publish financial statements for the period 2010-2018. The number of non-financial companies that meet the research criteria is 221. Hypothesis testing uses multiple regression models (multiple regression). The results of this study indicate that institutional ownership has a negative and significant effect on policy, meaning that institutional ownership can be a mechanism to reduce agency costs. Free cash flow also has a negative and significant effect on debt policy; this proves that the less free cash flow a company has in funding a company's investment, the higher the company will use its debt policy to fund its investment. While the size of the company does not affect debt policy, this proves that the larger the size of the company will not affect the capital structure in a company.